The feasibility and effectiveness of remote cognitive training on cognitive function and work performance in workers - Shibaoka, Michi; Masuda, Masashi; Iwasawa, Satoko; Ikezawa, Satoru; Eguchi, Hisashi; Nakagome, Kazuyuki (Frontiers in Psychology, 2024)
Objectives: We aimed to determine whether remote cognitive training (CT) is feasible and has the potential to improve cognitive function and work performance in Japanese workers. Methods: From June to September 2020, this intervention time series study enrolled workers aged 18-65 years from 10 companies located in a metropolitan area of Japan. Cognitive function tests and self-administered questionnaires were completed by the participants three times: at baseline, after 12 weeks of CT, and after a further 12 weeks following cessation. We measured work performance with the question: "How would you rate your performance (compared with your optimum performance) over the past 4 weeks?" Responses were made via a visual analog scale (0-100). Cognitive function was assessed using the THINC-integrated tool, which is a brief, objective computerized cognitive assessment battery. For our computerized remote CT intervention, BrainHQ was used on the basis of our scientific rationale and the empirical literature. We recommended three 20-minute sessions of BrainHQ per week and sent participants three reminders. Results: In total, 119 participants were recruited to this study. Only 22.7% of the subjects achieved the recommended training time of 720 minutes over 12 weeks. The median training time was used to divide participants into long and short-training groups. The long-training group showed a greater improvement in attention and executive function than the short-training group but there was no significant improvement in work performance after CT compared to baseline. Conclusions: Our results suggest that although remote CT was not feasible enough, the effects on cognitive function can be expected by increasing training time and motivation.